Models of Somatic Hypermutation Targeting and Substitution Based on Synonymous Mutations from High-Throughput Immunoglobulin Sequencing Data - Yaari, Gur; Vander Heiden, Jason; Uduman, Mohamed; Gadala-Maria, Daniel; Gupta, Namita; Stern, Joel N.; O'Connor, Kevin; Hafler, David; Laserson, Uri; Vigneault, Francois; Kleinstein, Steven (Frontiers in Immunology, 2013)
The abstract is in the manuscript document. We could not get the updated abstract to load properly.